Análise do programa de integridade do Ministério da Saúde - Souza, Joilma Farias de (2024)
The democratic rule of law is materialized through the primary role of the state, which is to serve the people. With the development of modern societies, service is increasingly sought beyond the provision of basic services, but rather the development of good public governance. While the principles of public governance qualify the constitutional principles, they also act to ensure the solidity and sustainability of public institutions and to restore public trust. In this sense, the public governance policy was introduced into the Brazilian public administration by Decree No. 9.203/2017, which established the structuring of governance, determining that the public bodies of the federal, direct, autarchic and foundational administration should structure their governance. Since the Integrity Program is one of the pillars of governance, the Ministry of Health instituted the Integrity Program in compliance with the Decree. With this in mind, the aim of the study was to analyze the Ministry of Health’s Integrity Program based on the regulations, benchmarks and national legislation applied to good governance. The study’s guiding questions are: to what extent is the Ministry of Health’s integrity program effective? What real contributions can be identified? What measures has the Ministry of Health adopted to minimize integrity risks in its processes? A qualitative research approach was adopted for this study, using document analysis and the content analysis technique. The results show that the Ministry of Health is complying with the program’s proposals and is actively working to strengthen the culture of integrity.